Flaxseed Nutritied Meat Balls With High Antioxidant Potential - Saleem, Hadia; Butt, Masood Sadiq; Shehzad, Aamir; Tanweer, Saira (Journal of Food Technology Research, 2014)
In the present era, nutraceutical foods have become a dietary inclination among consumers due to its health enhancing properties. Flaxseed is an important source of lignans which are phenolic compounds, linked to numerous health boosting effects against various life threatening ailments. To prevent different lifestyle disorders some antioxidant enriched foods must be included in our diet. To fulfill this requirement flaxseed enriched meat balls were prepared. Flaxseed bioactive moiety was obtained by using (3%) conventional solvent extraction system (T1) and with its comparison with (T2) supercritically extracted lignans (0.1%). Flaxseed fortified meat balls were analyzed for its physicochemical and the sensory evaluation. After properly frying the fortified balls color was investigated by CIELAB color system. The maximum L*and a* value was observed in supercritical extracted nutrified meat balls however, b*, chroma and hue angle was observed maximum in conventional solvent extracted enriched meat balls. The T2 balls also have better texture and maximum antioxidant activity among all the treatments. In the case of sensory attributes color and over all acceptability was maximum in T2 whist T1 was best in texture however taste was more appreciated in control treatment.